FLOWERING AND YIELD CHARACTERISTICS OF MACAPUNO BEARING DWARF X TALL COCONUT HYBRIDS - T. C. Nunez; V. M. de Paz (International Coconut Community, 1990)
Three macapuno‑bearing dwarf x tall coconut hybrid trees were observed to exhibit some characteristics influenced by the dwarf female parents. Flowering started as early as 39 to 57 months after planting. Intraspadix overlapping of 43 to 100% was also recorded suggesting moderate to high degree of self pollination. Macapuno yield ranged from 0‑50% per bunch. The nuts resemble the female parents in form but were generally heavier. They were all classified as type l macapuno. Binomial test showed goodness of fit to 3:1 ratio of normal to macapuno nuts.